2022
DOI: 10.1002/adom.202102790
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Lead Halide Nanocrystals based Flexible X‐Ray Imaging Screen and Visible Dose Rate Indication on Paper Substrate

Abstract: Metal halide semiconductors have huge potential on X‐ray detection, due to their high atomic number, adjustable photoluminescence wavelength, superior stability, and simple fabrication process. Here, cesium lead halide nanocrystals (CsPbX3 NCs) are fabricated on paper substrate as scintillator screen for the first time. By means of all‐solution processed spray‐coating method with optimization of polymethyl methacrylate, large‐area (>600 cm2) and low‐cost (0.0975 dollar cm−2) flexible scintillator screens are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Besides, the high PLQY of TADF effectively ensures the light out-coupling efficiency, enabling a high scintillation light yield. Generally, for the all-inorganic semiconductor scintillators, such as CsPbBr 3 and CdTe, [7,[46][47][48] there is a conflict between large Stokes shift and high luminescence efficiency. While, in the Cs 2 ZrCl 6 scintillators with TADF nature, both two desirable properties can be taken into account simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the high PLQY of TADF effectively ensures the light out-coupling efficiency, enabling a high scintillation light yield. Generally, for the all-inorganic semiconductor scintillators, such as CsPbBr 3 and CdTe, [7,[46][47][48] there is a conflict between large Stokes shift and high luminescence efficiency. While, in the Cs 2 ZrCl 6 scintillators with TADF nature, both two desirable properties can be taken into account simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a high X-ray imaging resolution of 18.3 lp mm -1 can be achieved, exceeding all the reported organic and most conventional inorganic scintillators. 10,[34][35][36][37][38][39] These findings provide a powerful design approach and promising new alternative materials for fabricating organic X-ray imaging scintillators with outstanding sensitivity, low cost, and high stability using a simple molecular engineering strategy involving TADF chromophores. TADF-H was selected as the preferred TADF system due to its large HOMO-LUMO separation, which largely minimizes the impact of heavy atoms on its TADF performance.…”
Section: Introductionmentioning
confidence: 92%
“…It can also be observed that the E g of CsPbCl 3 QDs is larger than CsPbBr 3 QDs in absorption spectra. [39] For the QDs layer, we further explore the effect on morphology of the CsPbI 3 film. The surface of CsPbI 3 film after annealing is nonuniform and contains many small pinholes, which can cause serious charge recombination.…”
Section: Resultsmentioning
confidence: 99%